Education-Engagement-Retention: the Gender Factor in Digital Illiteracy in Greece - Irene Kamberidou (Proceedings of European Commission Shadowing Conference, Women and Science: "Move out of the shadow! Seize the opportunITy", 2008)
DOI: 10.13140/RG.2.1.2821.0725 Full pdf (proceedings and article) in Research Gate (RG) --------------------------------------------------------------------------------------------------------- Gender-constrained educational choices, traditional-anachronistic perspectives, the life-work balance or rather imbalance, the lack of affordable child care facilities, the glass ceiling, the leaky pipeline, among other things, have contributed to the declining interest of Greek women in science and technology. This paper focuses on the factors that contribute to Greek women’s non-engagement or under-representation in ICT related fields, such as computing. It examines the gender-constrained institutions in Greece while providing an overview of the gender distribution in scientific research and in the Greek academia, where only about one third (27%) of the teaching staff in universities are women. Digital illiteracy has been detected amongst university students in Greece, over half of which are women, as well as amongst primary and secondary school teachers throughout the country who explicitly express a technophobic unwillingness to use computers in their classrooms, although they claim to agree on their significant educational value and usefulness. Although the Greek Ministry of Education had implemented the training of 76,000 teachers in ICTs, it seems to have failed to reach the aspired levels of effectiveness, in a society where the participation of women in the teaching profession—primary and secondary education—is over 50%. The majority of the respondents from rural, agricultural,  urban areas of Greece claim that they have not benefited by the technology classes or computer lessons they had received in high school, and not only. The gender variable plays a decisive role in the development of attitudes, i.e. the use of computers or the internet as a tool may be gender-neutral, however access to and motivation of use is gender-constrained. The Greek public school system’s inadequate technological infrastructures, deficiencies in the vocational orientation of students and the continuous techno-education of teachers, the lack of collaboration of the education system with the employment sector and the ICT industry— along with the family-career imbalance, namely the incompatibility of private life and career which is essentially a female problem— have made it impossible for the gender subject to keep up with the accelerated speed of technological developments. An ‘Education-Engagement-Retention Action Plan’ is required to change attitudes and promote women in science and technology, in the academia, etc.: (1) Child care facilities, flexi-hours, family support programmes, and a family-friendly working environment. (2) The establishment of an attractive open labour market that recruits and retains women in science and technology.